Les interactions langagières en maternelle : moment clé pour la révision des savoirs relatifs à l’écrit - Ariane Richard-Bossez (Recherches en Éducation)
This article questions how language interactions can be observed in kindergarten classes and the possibilities they open or close in terms of revising literacy knowledge. In the first part, the conditions that allow language interactions to take place in the classroom are examined. The second part focuses on the interactions that take place between students outside the teacher's presence and their role in the construction of knowledge. Finally, the last part focuses on the exchanges that take place between teachers and students, whether they are dual or collective, by questioning their effects on learning. In a transversal way, the purpose highlights the twofold dimension of language interactions in the classroom, which are both the source of cognitive processes and academic judgments on students. It leads to the formulation of several hypotheses concerning the process of revising knowledge that is played out in these interactions, particularly for students who do not initially use a literacy interpretation of educational activities and exchanges.